2006
DOI: 10.1080/01485010600822747
|View full text |Cite
|
Sign up to set email alerts
|

Antisperm Antibodies in Prepubertal Boys With Cryptorchidism

Abstract: The presence of antisperm antibodies in male individuals before puberty is controversial due to the lack of finally differentiated male germ cells. It was questioned whether the pathologic conditions of the male gonad may influence antisperm antibody formation in individuals before puberty. Sera samples of 76 individuals and 10 healthy boys with testicular failure (mainly uni- or bilateral cryptorchidism) were examined by means of indirect immunobead-binding test (IDIBT). The presence of antisperm antibodies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
1
4
1
Order By: Relevance
“…The precise mechanisms accounting for this clinical phenomenon are surrounded by controversies. ASA has been proposed to act as an active participator in the pathogenesis of cryptorchidism-associated infertility [9,14]. However, the present study failed to prove a significant level of ASA in the infertile males with a history of cryptorchidism.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The precise mechanisms accounting for this clinical phenomenon are surrounded by controversies. ASA has been proposed to act as an active participator in the pathogenesis of cryptorchidism-associated infertility [9,14]. However, the present study failed to prove a significant level of ASA in the infertile males with a history of cryptorchidism.…”
Section: Discussioncontrasting
confidence: 54%
“…However, data pertaining to the formation of ASA in cryptorchid males is conflicting. Several studies have revealed a high incidence of ASA in prepubertal boys with cryptorchidism [5,9]. ASA was even thought to emerge as an inherent characteristic in cryptorchids independent of their undescended testis location and orchidopexy treatment [10].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there are differences in the literature in ASA measurements intended to clarify the role of autoimmunity in the likely cause of sub‐/infertility in children with UDT. For instance, the reported ASA positivity range was 25% of boys who underwent orchidopexy, 18 13.8% of boys with UDT, 19 and 3.95% of prepubertal boys with UDT 17 . In our study, ASA was determined at a level of 20.5% in the UDT group and 13.6% in healthy individuals.…”
Section: Discussionsupporting
confidence: 41%
“…They have been found in the blood and seminal fluid of men with UDT. However, the presence of ASA as such in sexually immature boys remains a controversial issue 5,17 . Indeed, there are differences in the literature in ASA measurements intended to clarify the role of autoimmunity in the likely cause of sub‐/infertility in children with UDT.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, anti-sperm antibodies (AsA) in serum samples from prepubertal boys were reported [7,8], and our earlier findings showed that cryptorchidism may play an important role in antibody formation at this age [9-11]. The human major histocompatibility complex Class II HLA molecules, by presenting antigens to helper T cells, play a decisive role in induction of antibody production [12].…”
Section: Introductionmentioning
confidence: 99%